Hypertrophic Lichen Planus with Histological Features of Squamous Cell Carcinoma Associated with Immune Checkpoint Blockade Therapy. (19th February 2020) - Ameri, Amir H.; Foreman, Ruth K.; Vedak, Priyanka; Chen, Steven; Miller, David M.; Demehri, Shadmehr
Abstract: : Immune checkpoint blockade (ICB) is highly effective for the treatment of metastatic cancers, but its side effects are incompletely understood. The objective of this article is to highlight hypertrophic lichen planus (HLP) with histological features diagnosed as squamous cell carcinoma (SCC), which is a potential cutaneous reaction to ICB. Two patients (75 and 69 years) presented with lesions diagnosed as SCC on biopsy, which developed after 3–9 months on ICB therapy. Biopsies demonstrated endophytic, atypical, or cystic squamous proliferations consistent with cutaneous SCC. However, the clinical presentation including monomorphic nature of the lesions and lichenoid inflammation in the background were consistent with HLP. Patients initially received topical 5‐fluorouracil (5‐FU) to reduce the hyperkeratotic lesions followed by topical steroids. The eruptions readily responded to this treatment regimen. Dermatologic immune‐related adverse events (irAEs) are the most common irAEs associated with ICB therapy. Our findings indicate that HLP resembling SCC on biopsy is a potential side effect of ICB that can be correctly diagnosed on careful clinical exam and is responsive to ICB cessation and topical steroid with or without 5‐FU treatment. Key Points : Immune checkpoint blockade is associated with cutaneous immune‐related adverse events including lichen planus. Hypertrophic lichen planus can appear as squamous cell carcinoma histologically and clinical context is key for the proper diagnosis. Hypertrophic lichen planus can be safely treated with topical steroids with or without topical 5‐fluorouracil in cases with severe hyperkeratotic lesions. Immune checkpoint blockade may be safely continued if clinical presentation is consistent with hypertrophic lichen planus. Abstract : Immune checkpoint blockade immunotherapy has revolutionized cancer treatment but is associated with dermatologic adverse events. This brief report highlights hypertrophic lichen planus with histological features diagnosed as squamous cell carcinoma on biopsy, featuring two successfully treated patients.